Problem dan Tranformasi Politik dan Penegakan Hukum di Indonesia - M Syafi’ie M Syafi’ie (UIN Sunan Kalijaga Yogyakarta, 2013)
Formulation law that production via mikanisme politics as well as lawenforcement in hand all very vulnerable law enforcer by abuse. Formulation law made legislative and government often deny social interest and built than just on the basis of interest all manager capital and the authorities that otoritarian. Among law product example that have a problem is rule in New Orde era namely UU. No. 8 year 1985 about principle is single, UU Subversi, Instruksion President No 14 year 1967 about religion, trust, China Customs, Decision Presidium No 127/U/Kep/12/1966 on Substitute Name for WNI Use Name China, and few others. Post- rule reformation, formulation Law that is full crisis is Law that related to Natural Resource. While in level law enforcement, the problem seen from law enforcer apparatus that is corrupt, decision law which left interest humanity and justice, and booming fact trade article.Because problematika need dingatkan constantly that formulator profession and law enforcement not off from morality, ethic and community social accountability.